2022
DOI: 10.1038/s41390-022-02071-2
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic beyond the virus: maternal COVID-related postnatal stress is associated with infant temperament

Abstract: Background Studies have shown that infant temperament varies with maternal psychosocial factors, in utero illness, and environmental stressors. We predicted that the pandemic would shape infant temperament through maternal SARS-CoV-2 infection during pregnancy and/or maternal postnatal stress. To test this, we examined associations among infant temperament, maternal prenatal SARS-CoV-2 infection, maternal postnatal stress, and postnatal COVID-related life disruptions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 38 publications
(44 reference statements)
6
16
0
Order By: Relevance
“…Our findings of altered brain connectivity agree with previous findings of altered brain connectivity in infants of mothers who reported higher stress during the pandemic[15]. Behavioral and functional deficits particularly in the motor, cognitive and temperamental domain have been widely reported in various studies investigating the impact of maternal stress during the pandemic on child outcomes [7,8,13,14]. Increased maternal stress and anxiety traits (outside the setting of the pandemic) have been shown to alter functional architecture of the fetal brain[47].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings of altered brain connectivity agree with previous findings of altered brain connectivity in infants of mothers who reported higher stress during the pandemic[15]. Behavioral and functional deficits particularly in the motor, cognitive and temperamental domain have been widely reported in various studies investigating the impact of maternal stress during the pandemic on child outcomes [7,8,13,14]. Increased maternal stress and anxiety traits (outside the setting of the pandemic) have been shown to alter functional architecture of the fetal brain[47].…”
Section: Discussionsupporting
confidence: 91%
“…Studies of infants born during the COVID-19 pandemic have reported reduced cognitive, motor, and emotional development compared to those born pre-pandemic [7,8], with increased prenatal stress directly associated with adverse effect and temperament [13,14]. Simultaneously, changes to brain structure and function have also been reported in infants born during the pandemic [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that stress during pregnancy can influence placental health and long‐term child development 4,16–20 . In terms of the COVID‐19 pandemic, the vast majority of the work has been focused on the impact of the infection, without taking into consideration the potential immune contribution of pandemic‐associated stress.…”
Section: Introductionmentioning
confidence: 99%
“…15 It is known that stress during pregnancy can influence placental health and long-term child development. 4,[16][17][18][19][20] In terms of the COVID-19 pandemic, the vast majority of the work has been focused on the impact of the infection, without taking into consideration the potential immune contribution of pandemic-associated stress. Of interest, Shuffrey et al investigated neurodevelopment at 6 months of age following maternal SARS-CoV-2 infection during pregnancy and observed differences regardless of infection status, which emphasise the role that pandemic stress has on fetal health.…”
Section: Introductionmentioning
confidence: 99%